A Chinese Chan-based lifestyle intervention improves memory of older adults - Chan, Agnes S.; Sze, Sophia L; Woo, Jean; Yu, Ruby H (Frontiers in Aging Neuroscience, 2014)
This study aims to explore the potential benefits of a Chinese Chan-based lifestyle intervention on enhancing memory in older people with lower memory function. Forty-four aged 60 to 83 adults with various level of memory ability participated in the study. Their memories (including verbal and visual components) were assessed before and after a 3-month intervention. The intervention consisted of 12 sessions, with one 90-minute session per week. The intervention involved components of adopting a special vegetarian diet, practicing a type of mind-body exercises and learning self-realization. Elderly with lower memory function at the baseline (i.e., their performance on standardized memory tests was within 25th percentile) showed a significant memory improvement after the intervention. Their verbal and visual memory performance has showed 50% and 49% enhancement respectively. In addition, their improvement can be considered as a reliable and clinically significant change as reflected by their significant pre-post differences and reliable change indices. Such robust treatment effect was found to be specific to memory functions, but less influencing on the other cognitive functions. These preliminary encouraging results have shed some light on the potential applicability of the Chinese Chan-based lifestyle intervention as a method for enhancing memory in the elderly population.